Evaluation of the Enzymatic Arsenal Secreted by Myceliophthora thermophila During Growth on Sugarcane Bagasse With a Focus on LPMOs - Grieco, Maria Angela B.; Haon, Mireille; Grisel, Sacha; de Oliveira-Carvalho, Ana Lucia; Magalhães, Augusto Vieira; Zingali, Russolina B.; Pereira, Nei; Berrin, Jean-Guy (Frontiers in Bioengineering and Biotechnology, 2020)
The high demand for energy and the increase of the greenhouse effect propel the necessity to develop new technologies to efficiently deconstruct the lignocellulosic materials into sugars monomers. Sugarcane bagasse is a rich polysaccharide residue from sugar and alcohol industries. The thermophilic fungus Myceliophthora thermophila (syn. Sporotrichum thermophilum) is an interesting model to study the enzymatic degradation of biomass. The genome of M. thermophila encodes an extensive repertoire of cellulolytic enzymes including 23 lytic polysaccharide monooxygenases (LPMOs) from the Auxiliary Activity family 9 (AA9), which are known to oxidatively cleave the β-1,4 bonds and boost the cellulose conversion in a biorefinery context. To achieve a deeper understanding of the enzymatic capabilities of M. thermophila on sugarcane bagasse, we pretreated this lignocellulosic residue with different methods leading to solids with various cellulose/hemicellulose/lignin proportions and grew M. thermophila on these substrates. The secreted proteins were analyzed using proteomics taking advantage of two mass spectrometry methodologies. This approach unraveled the secretion of many CAZymes belonging to the Glycosyl Hydrolase (GH) and AA classes including several LPMOs that may contribute to the biomass degradation observed during fungal growth. Two AA9 LPMOs, called MtLPMO9B and MtLPMO9H, were selected from secretomic data and enzymatically characterized. Although MtLPMO9B and MtLPMO9H were both active on cellulose, they differed in terms of optimum temperatures and regioselectivity releasing either C1 or C1-C4 oxidized oligosaccharides, respectively. LPMO activities were also measured on sugarcane bagasse substrates with different levels of complexity. The boosting effect of these LPMOs on bagasse sugarcane saccharification by a Trichoderma reesei commercial cocktail was also observed. The partially delignified bagasse was the best substrate considering the oxidized oligosaccharides released and the acid treated bagasse was the best one in terms of saccharification boost.